2008
DOI: 10.1182/blood-2007-09-114231
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic features of acute lymphoblastic and myeloid leukemias in pediatric patients with Down syndrome: an iBFM-SG study

Abstract: Children with Down syndrome (DS) have a markedly increased risk of acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). To identify chromosomal changes cooperating with ؉21 that may provide information on the pathogenesis of these leukemias, we analyzed 215 DS-ALLs and 189 DS-AMLs. Unlike previous smaller series, a significant proportion of DS-ALLs had the typical B-cell precursor ALL abnormalities high hyperdiploidy (HeH; 11%) and t(12;21)(p13;q22) (10%). The HeH DS-ALLs were characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(190 citation statements)
references
References 64 publications
7
176
3
3
Order By: Relevance
“…In their recent review of 215 DS-ALLs, Forestier et al observed that a significant proportion of DS-ALL patients had typical B-cell precursor ALL abnormalities, including high hyperdiploidy (11%) and t(12;21) (10%). 25 Altogether, these findings clearly support the concept, recently reviewed by Hasle, 1 that leukemia in DS results in most cases from a different pathway than in non-DS subjects. In only a minority of DS patients, leukemia may occur as a ''random'' event and thus behave as in non-DS subjects.…”
Section: Discussionsupporting
confidence: 75%
“…In their recent review of 215 DS-ALLs, Forestier et al observed that a significant proportion of DS-ALL patients had typical B-cell precursor ALL abnormalities, including high hyperdiploidy (11%) and t(12;21) (10%). 25 Altogether, these findings clearly support the concept, recently reviewed by Hasle, 1 that leukemia in DS results in most cases from a different pathway than in non-DS subjects. In only a minority of DS patients, leukemia may occur as a ''random'' event and thus behave as in non-DS subjects.…”
Section: Discussionsupporting
confidence: 75%
“…The study showed the feasibility of reduced use of cranial irradiation, 4 emphasized that host pharmacogenetics influence the cure rate, 5 confirmed the importance of myelosuppression during maintenance therapy, 6 showed that MTX/6MP maintenance therapy is important for high-risk (HR) ALL, 7 and allowed mapping of the epidemiological and clinical characteristics of several cytogenetically defined subsets of ALL. [8][9][10][11][12][13][14] The goals of the subsequent common NOPHO ALL-2000 protocol were to examine the efficacy of Vincristine (VCR)/Dexamethasone reinductions during maintenance therapy and to examine the feasibility of non-centralized minimal residual disease (MRD) monitoring by flow cytometry and PCR. [15][16][17][18][19] The ALL-92 and ALL-2000 studies have paved the way to total elimination of prophylactic cranial irradiation in the current ALL-2008 protocol and to implementation of a treatment stratification primarily based on cytogenetics and early MRD monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…73,75 A striking observation is that CRLF2 alteration, most commonly the PAR1 deletion, is present in over 50% of ALL associated with Down's syndrome (DS-ALL), 61,74 in which other chromosomal rearrangements characteristic of childhood ALL are uncommon. 76 The basis for this increased frequency in DS-ALL is currently unknown.…”
Section: Genetic Characterization Of Bcr-abl1-like Phà Allmentioning
confidence: 99%